Reducing Subjectivism in Solving Project Management Problems - Igor, Neroslavsky (Current Aspects in Business, Economics and Finance Vol. 10, 2023)
When working on projects, teams quite often have to deal with non-formalizable problems that can significantly affect the success of the project as a whole. The decisions made in such cases are often subjective. To reduce the share of subjectivism, it is proposed to use the analytic hierarchy process proposed by T. Saaty, which refers to complex examinations. The article describes in detail the procedure for choosing a project manager (and in a broader sense - a manager or specialist), which leads to a decrease in the subjectivity of such a choice.